STUDENT PERSONALITY AS A SUBJECT INDEPENDENT LEARNING ACTIVITY IN CONDITIONS HIGHER PEDAGOGICAL EDUCATIONAL INSTITUTION (Pedagogy of Higher and Secondary Education, 2022)
The article deals with a personality of the student as the subject of self directed learning activities under conditions of a higher teacher training institution.